Analisis Peran Business Process Excellence Dalam Meningkatkan Kualitas Dokumentasi Instruksi Kerja di PT. Semen Indonesia (Persero) Tbk. - Rangga Meulligga Daniarko; Nurhadi Nurhadi (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research is motivated by the need of PT Semen Indonesia (Persero) Tbk. to improve the quality of work instruction documentation in order to achieve uniformity, efficiency, and compliance with stringent regulations. Inconsistent documentation quality can lead to operational inefficiencies and increased risk of workplace accidents. Therefore, the company has adopted an approach involving the Business Process Excellence (BPE) department to improve and refine work instruction documentation. This research employs a qualitative descriptive method with data collection techniques including field observations, interviews with relevant sources, and documentation. Primary data were obtained from observations and interviews, while secondary data were sourced from books, journals, and websites. Data analysis was conducted using a descriptive-narrative technique. The research findings indicate that the implementation of BPE has successfully enhanced documentation quality through three stages: review and evaluation, development and refinement, and continuous monitoring and evaluation.